Perancangan Pemanenan Hujan untuk Penyediaan Air Bersih dan Pengurangan Aliran Permukaan di Pasar Datah Manuah - I Made Kamiana; Allan Restu Jaya; Ozy Saputera (Department of Civil Engineering and Planning, Faculty of Engineering, Sriwijaya University, 2026)
Pasar Datah Manuah is one of the largest traditional markets in Palangka Raya. During heavy rainfall with a long duration, the water level in the drainage channels outside the market area rises quickly, while the drainage channels inside the market building often experience flooding. This situation leads to ponding in several areas of the market courtyard. One alternative solution to this problem is the implementation of a rainwater harvesting system. This study aims to design rainwater storage components for three large buildings in Pasar Datah Manuah. The rainwater storage is designed to serve as an alternative source of clean water while also reducing peak surface runoff. The storage volume is designed by comparing the cumulative rainwater supply with the cumulative clean water demand. Peak surface runoff analysis uses the Rational Method. The study results show that to meet the daily clean water needs for the three buildings with a floor area of 4,806 m², a rainwater storage volume of 74.87 m³ is required. The study also indicates that the average peak surface runoff, calculated at two drainage outlets in the market courtyard, reaches 0.36 m³/s without the rainwater harvesting scenario. With the rainwater harvesting scenario, the average peak runoff decreases to 0.27 m³/s. In other words, under the rainwater harvesting scenario, the average peak surface runoff at the market courtyard outlets decreases by 25.95%.